Citra Merek dan Brand Ambassador terhadap Keputusan Pembelian Mie Sedap Korean Spicy Chicken - Sultan Maulana Yusuf; Siti Aminah (Journal of Management and Bussines (JOMB), 2023)
This research aims to analyze the influence of brand image and brand ambassadors on the decision to purchase Korean Spicy Chicken Noodles among students at the National Development University "Veteran" East Java. The following research method is quantitative. SEM (Structural Equation Modeling) is a data analysis method that relies on elements and uses PLS (Partial Least Squares) analysis equipment. Research Results a) the Brand Image variable in Purchasing Decisions has path coefficients of 0.201926, a T-statistic score of 2.543859 > 1.96 (from the table score Zα = 0.05), and a P-Value of 0.012 < 0.05; b) the Brand Ambassador variable (X2) in Purchasing Decisions (Y) has a path coefficient value of 0.433517, a T-statistic score of 6.004843 > 1.96 (from the table score Zα = 0.05), and a P-Value of 0.000 < 0.05. In conclusion, brand image and brand ambassadors have a statistically significant and positive effect on purchasing decisions for Korean spicy chicken noodles. Keywords: Brand Ambassador, Brand Image, Purchase Decision